Diversity of Diurnal Butterflies (Lepidoptera) in Three Different Habitats in Batutegi Protected Forest, Lampung - Hasni Ruslan; Sumayyah Sumayyah; Reza Taufiq Darmawan; Alena Puspa Murti; Regitha Cahyani; Wirayudho Birowo (Al-Kauniyah: Jurnal Biologi, 2025)
AbstractBatutegi protected forest has various ecosystems that are habitat for butterfly species despite being largely unexplored. This study aimed to investigate the diversity of diurnal butterflies in three different habitats of Batutegi Protected Forest, Lampung. Sampling using exploration methods was conducted in forest, river, and swamp habitat. The results showed that swamp habitat had 28 species, river habitat had 19 species, and forest habitat had 20 species. Shannon-Wiener diversity index for all habitat was at moderate level. Hutchinson's t-test results showed diversity index between three habitats was significantly different. Evenness index was at high level. The Nymphalidae family had the greatest number of species and individuals, while Lycaenidae and Riodinidae had the least. Eurema hecabe was found the highest in swamp vegetation. Cupha erymanthis was found the highest in river vegetation. Euthalia monina was found the highest in forest vegetation. Two protected species, Trogonoptera brookiana and Troides helena, were observed. Butterfly diversity was affected by habitat condition. This study can serve as fundamental reference in determining vegetation suitability for stabilizing Batutegi Protected Forest for educational and ecotourism purposes.AbstrakHutan Lindung Batutegi memiliki beragam ekosistem yang menjadi habitat spesies kupu-kupu. Penelitian ini bertujuan untuk mengetahui keanekaragaman jenis kupu-kupu di tiga habitat Hutan Lindung Batutegi, Lampung.  Pengambilan data dilakukan dengan metode eksplorasi di habitat rawa, sungai dan hutan. Jumlah spesies kupu-kupu ditemukan terbanyak pada habitat rawa sebanyak 28 spesies, spesies kupu-kupu di habitat hutan sebanyak 20 spesies, dan di habitat sungai sebanyak 19 spesies. Komposisi spesies kupu-kupu yang terdapat di habitat rawa dan sungai memiliki tingkat kesamaan yang tinggi. Indeks keanekaragaman kupu-kupu pada tiga habitat tergolong sedang. Hasil uji Hutchinson menunjukkan perbedaan bermakna antar habitat. Indeks kemerataan kupu-kupu di tiga habitat bernilai tinggi. Famili Nymphalidae memiliki spesies dan individu terbanyak, sedangkan famili Lycaenidae dan Riodinidae paling sedikit. Eurema hecabe ditemukan terbanyak di habitat rawa. Cupha erymanthis ditemukan terbanyak di habitat sungai. Euthalia monina ditemukan terbanyak di habitat hutan. Terdapat dua spesies kupu-kupu yang dilindungi, yaitu Troides helena dan Trogonoptera brookiana. Keanekaragaman kupu-kupu dipengaruhi oleh kondisi habitat. Penelitian ini dapat digunakan sebagai dasar pertimbangan kesesuaian habitat yang  perlu dipertahankan untuk menyeimbangkan daerah kawasan Hutan Lindung Batutegi sebagai sarana edukasi  dan ekowisata.